2011
DOI: 10.3109/13697137.2010.498594
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of efficacy ofDiascorea alatafor menopausal symptom treatment in Taiwanese women

Abstract: Compared with placebo, Diascorea alata improves symptoms, particularly the psychological parameters in menopausal women. Safety monitoring indicated that standardized extracts of Diascorea alata were safe during daily administration over a period of 12 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 30 publications
1
27
0
3
Order By: Relevance
“…In menopausal women, extracts of blue green algae ( Aphanizomenon flos‐aquae ) (Genazzani et al, ), Cimicifuga foetida (Zheng et al, ), grape seed ( Vitis vinifera ; Terauchi et al, ), rhapontic rhubarb ( Rheum rhaponticum ; Kaszkin‐Bettag et al, ), rose tea (Tseng, Chen, & Yang, ), and wild yam ( Dioscorea alata ; Hsu, Kuo, Chang, Wu, & Huang, ) helped decrease symptom scores related to anxiety and depression. Whereas wild yam appears to work via estrogenic pathway, the blue green algae extract did not demonstrate any hormonal effects.…”
Section: Resultsmentioning
confidence: 99%
“…In menopausal women, extracts of blue green algae ( Aphanizomenon flos‐aquae ) (Genazzani et al, ), Cimicifuga foetida (Zheng et al, ), grape seed ( Vitis vinifera ; Terauchi et al, ), rhapontic rhubarb ( Rheum rhaponticum ; Kaszkin‐Bettag et al, ), rose tea (Tseng, Chen, & Yang, ), and wild yam ( Dioscorea alata ; Hsu, Kuo, Chang, Wu, & Huang, ) helped decrease symptom scores related to anxiety and depression. Whereas wild yam appears to work via estrogenic pathway, the blue green algae extract did not demonstrate any hormonal effects.…”
Section: Resultsmentioning
confidence: 99%
“…The data of this study showed that after intervention, there was statistical significant decrease in the progesterone and the FSH levels, and significant increase in the estradiol E2 concentration while no statistical significance in the levels of the free testosterone. In this context, results of a study conducted by Hsu et al (2011), among Taiwanese menopausal women, were also shown elevated serum estradiol and dehydroepiandrosterone sulfate (DHEAS) levels, and decreased FSH concentration in those who ingested Diascorea (tuber contains beta-sitosterol, stigmasterol, 22-23-dihydro-, and γ-sitosterol). It has been reported that the chemical similarity between 17β-estradiol and phytoestrogens confers the capability to interact with estrogen receptors (ERs).…”
Section: Discussionmentioning
confidence: 99%
“…Òàê, ó ñòàðûõ ñàìîê êðûñ íàéäåíî, ÷òî ïåðî-ðàëüíîå ââåäåíèå äèîñãåíèíà (10 èëè 50 ìã/êã/äåíü ïåðîðàëüíî) â òå÷åíèå 8 íåäåëü ñóùåñòâåííî òîðìîçèò ðàñïàä òðàáåêóëÿðíîé ñòðóêòóðû òêàíè áåäðåííîé êîñòè, à òàêaeå çíà÷èòåëüíî óìåíüøàåò îáúåì îáëàñòåé êîñòíîé òêàíè, ïîðàaeåííûõ îñòåîïîðîçîì, ïî ñðàâíå-íèþ ñ êîíòðîëüíîé ãðóïïîé [31,40].…”
Section: âëèÿíèå äèîñãåíèíà è ýêñòðàêòà êîðíåé äèîñêîðåè (äèêèé ÿìñ) unclassified
“…Ïðåäïîëàãà-þò, ÷òî êîððåãèðóþùèå ýôôåêòû äèîñãåíèíà èëè ýêñ-òðàêòà êîðíåé äèîñêîðåè íà íåðâíî-ïñèõè÷åñêèå è ýí-äîêðèííî-îáìåííûå íàðóøåíèÿ ó aeåíùèí ïðè êëèìàêñå íå ñâÿçàíû ñ èõ ïðÿìûì ãîðìîíîïîäîáíûì äåéñòâèåì, à ÿâëÿþòñÿ îïîñðåäîâàííûì ðåçóëüòàòîì êàñêàäà íåçàâèñèìûõ, åùå íå èçó÷åííûõ ìîëåêóëÿð-íî-áèîõèìè÷åñêèõ ñîáûòèé, êîòîðûå ñóùåñòâåííî óëó÷øàþò îáùåå ñîñòîÿíèå îðãàíèçìà aeåíùèíû â ïå-ðèîä ìåíîïàóçû [28,31,39]. Âìåñòå ñ òåì ýêñïåðèìåí-òàëüíûå äàííûå è êëèíè÷åñêèå íàáëþäåíèÿ ãîâîðÿò î òîì, ÷òî â îòëè÷èå îò ôèòîýñòðîãåíîâ, êîòîðûå òîëüêî èìèòèðóþò ýôôåêòû ýíäîãåííûõ ýñòðîãåíîâ â îðãà-íèçìå aeåíùèíû â ïåðèîä ìåíîïàóçû, ôèòîñàïîíèíû ìîãóò ïðîÿâëÿòü áîëüøóþ øèðîòó ôàðìàêîëîãè÷åñêî-ãî âîçäåéñòâèÿ íà ðåïðîäóêòèâíûé ïðîôèëü ïðè äåôè-öèòå ýñòðîãåíîâ çà ñ÷åò èõ ñòðóêòóðíîãî ñõîäñòâà ñ äå-ãèäðîýïèàíäðîñòåðîíîì.…”
Section: âëèÿíèå äèîñãåíèíà è ýêñòðàêòà êîðíåé äèîñêîðåè (äèêèé ÿìñ) unclassified
See 1 more Smart Citation